Analysis of mental and physical fatigue over the course of a professional English Premier League season in outfield players - Brett, Adam; Rhodes, David; Grimson, Sophie; Kiely, John (Biology of Sport, 2025)
A variety of studies suggest mental fatigue (MF) negatively influences both perceptions of physical fatigue and psychomotor performance. No prior investigation has examined potential changes in player ratings of MF over the course of an English Premier League (EPL) season. This study analysed how MF and PF varied among elite footballers, at both grouped and individual levels, across a 46 match EPL season. Prospective cohort study. Over the course of a 40-week, 151 training sessions and 46 games season, 21 first team male EPL footballers rated both physical fatigue (PF) and MF on a 100-mm visual analogue scale on match day minus-one (M-1). No significant group differences were established for MF (18.9±13.0 vs. 17.8±14.8 vs. 20.8±20.5) and PF (21.4±14.0 vs. 20.9±14.7 vs. 19.9±17.5) ( P > 0.05) between early, mid and late season timepoints. However, pervasive individual differences were evident across timescales. Unlike earlier comparable work in netball, this study did not detect group-based changes in MF or PF over a competitive season. However, extensive changes in individual ratings of MF and PF did occur. This study highlights the potential importance of monitoring and managing MF trends within squads of elite footballers. The 100-mm visual analogue scale provides practitioners with a pragmatic tool capable of, in a resource-efficient manner, monitoring MF in EPL sqads. Monitoring MF potentially facilitates the customised provision of targeted remediation strategies encompassing (a) training design, (b) individualized recovery and (c) player education relating to MF alleviation and stress management interventions.